Risk factors associated with low back pain in rowers: a systematic review and meta-analysis - Xu Ze; Shuo Zhang; Xingnian Long; Peng Zhou (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Low back pain (LBP) is a prevalent injury among rowers, impacting their careers and potentially causing disability. However, the risk factors for LBP in rowers are still unclear, with most existing studies focusing on individual factors and lacking comprehensive meta-analyses. Methods This systematic review and meta-analysis, following PRISMA guidelines, conducted comprehensive searches in PubMed, Web of Science, Embase, and Medrxiv without publication date restrictions. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated using a random-effects model to account for heterogeneity. Sensitivity analyses assessed result robustness by excluding individual studies, and meta-regression explored potential heterogeneity sources. The study protocol was registered in PROSPERO (CRD42024590865). Results A total of 2,081articles were retrieved, and 10 studies (N = 2,082) were included in the analysis after screening. These comprised 7 cross-sectional and 3 cohort studies, with an average quality score of 7.4. Meta-analysis results showed that age (OR = 1.05, 95% CI: 0.98–1.12), sex (OR = 1.37, 95% CI: 0.63–2.95), BMI (OR = 1.00, 95% CI: 0.91–1.11), competitive level (OR = 1.45, 95% CI: 0.86–2.45), training volume (OR = 1.26, 95% CI: 0.83–1.91), rowing type (OR = 0.69, 95% CI: 0.21–2.25), and Number of years rowing (OR = 1.02, 95% CI: 0.92–1.13) were not significantly associated with low back pain (LBP) in rowers. In contrast, a history of previous LBP (OR = 2.65, 95% CI: 1.86–3.78) was significantly associated with LBP in this population. Conclusion Previous low back pain (LBP) is significantly associated with LBP in rowers. Future work requires more high-quality prospective studies to elucidate risk factors and support evidence-based prevention and rehabilitation strategies for rowers.